Kewenangan dan Kedudukan Dinas Syariat Islam Dalam Tata Kelola Pemerintahan Aceh - muhammad isa; Kushandajani .; puji astuti (Journal of Politic and Government Studies, 2016)
This study was conducted to determine how the relationship between institutions andenforcement of Syariat Islam in Aceh as well how the process of cooperation as well as theseparation of powers between the relevant institutions. The objectives to be achieved in thisresearch is to identify and analyze the role of the Department of Syariat Islam and itsposition in the governance of Aceh. This type of research is qualitative descriptive researchtype with survey research, by analyzing data in the field on a direct source in the form ofwords, the picture is not numbers, data obtained include interviews, field notes, documentsand so on others. This study aims to describe, summarize a variety of conditions, varioussituations that arise on implementation of Islamic Law in Aceh local governance which is theobject of this study, based on what happened then raised to the surface of the character /picture of conditions and circumstances. The focus of research is the Islamic Lawenforcement agencies in Aceh who participated in providing support and assist theDepartment in enforcing the Syariat Islamic Law.From the data processing research showed that the relationship of the Department ofSyariat Islam in Aceh with the relevant institutions have close cooperation and mutualsupport in the enforcement of Shariah. Cooperation between the Department of Islamic Lawwith the relevant institutions have been better when compared to previously where therelevant institutions to help the enforcement of Syariat Islam only as guidance only, but nowthe Department of Islamic Law together with the relevant institutions can conduct training,investigation, interrogation until the execution which will be performed by the judiciary ofSyariat Islam law in Aceh on the legality and authority he had. Socialization provided by thegovernment of Aceh has also been quite good, with a positive response from the people ofAceh and the Aceh government's support of the enforcement of Syariat Islam in Kaffah torealitation.Keywords : Authority of Syariat Islam, Place of Syariat Islam,The Judiciary of Aceh, Acehgovernment.